Beyond Virtuosity: Reconsidering the Compositional Autonomy of Agustín Barrios Mangoré and the Performer-Composer Binary in Classical Guitar Scholarship - A Case Study of La Catedral - Lim Chien Hu; Herry Rizal Djahwasi; Zaharul Lailiddin bin Saidon (Grenek: Jurnal Seni Musik, 2026)
Agustín Barrios Mangoré (1885–1944) is frequently described in classical guitar scholarship as a “performer-composer,” yet this category often remains undertheorized. This article argues that the label carries assumptions shaped by the Romantic work-concept, which privileges composition as authoritative and treats performance as secondary. Such a framework risks reducing Barrios’s compositional thought to virtuoso technique and judging his music through European canonical standards. Drawing on Lydia Goehr’s theory of the historically constructed work-concept and Nicholas Cook’s idea of performance-as-analysis, this study examines La Catedral (1921/1938). The analysis identifies structural decisions that exceed idiomatic guitar writing: the harmonic voice-leading of Preludio Saudade, the three-voice Baroque counterpoint of Andante Religioso, and the chromatically intensified formal design of Allegro Solemne. The article concludes that Barrios’s music demonstrates compositional intelligence grounded in performance but not subordinated to it, offering a broader model for evaluating non-European classical guitar repertories.